Managing hot flushes and night sweats : a cognitive behavioural self-help guide to the menopause - Hunter, Myra; Smith, Melanie, 1975- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This revised edition of Managing Hot flushes and Night Sweats offers up to date and evidence-based information about the menopause and about hot flushes and night sweats, which are the main reason that women seek medical help. The four-week self-help guide uses cognitive behavior therapy providing information and strategies for managing hot flushes and night sweats, as well as stress and sleep. The guide is interactive with exercises and homework tailored to women's individual circumstances and lifestyles. It challenges myths about menopause and aging and provides better understanding of flushes which in turn reduces stress and improves post-menopausal wellbeing. The various chapters discuss processes of identification and modification of triggers of hot flushes and offers tips to women on dealing with hot flushes in social and work situations. The guide was as effective as eight hours of group CBT and would help women who want to try a non-medical treatment that is brief, effective without side effects, or just want to be better informed"--
OCLC-licensed vendor bibliographic record.
Keywords: Menopause -- Popular works; Cognitive therapy -- Popular works; Self-care, Health -- Popular works; HEALTH & FITNESS / Women's Health; PSYCHOLOGY / Psychotherapy / Counseling